Frankenstein's footsteps : science, genetics and popular culture - Turney, Jon (Yale University Press, 1998)
Discusses the influences of Mary Shelley's Frankenstein and other works of literature on public attitudes towards biotechnology and scientific development over the last two centuries and compares them to the reality of the current controversies.